Analisis Penerapan Manajemen Proyek dalam Perencanaan Instalasi Pengolahan Air Limbah (IPAL) di Perkotaan (Studi Kasus di Kawasan Tb. Simatupang) - Rachmatama, Riesky; Azhar, Moh. (Universitas Batanghari Jambi, 2024)
Urban WWTP development in the Simatupang area will integrating water life cycle, from managing waste water flow to reservoir, and then the raw water will be treated for drinking water. The most important effluent of waste water must be store first in the reservoir, and then treated for drinking water; it is possible direct converted from waste water to drinking water, however, the culture and religion of the community was not accepted. Construction of WWTP will be applied for business/mixuse area along 8 km and utilize 9 Ha land in the commercial area. The formulation of the problem of analyzing the application of project management in urban WWTP planning in the TB Simatupang area, is how the application of project management can affect the smoothness and success of the planning process for Urban WWTP development in the TB Simatupang area. In this problem formulation, the focus is placed on the effect of project management implementation on Simatupang WWTP planning. This led to research on evaluating the project management steps taken and their impact on the smoothness and success of the WWTP planning.